IMPROVING HIGHER EDUCATION INVOLVEMENT IN EDUCATIONAL COMMUNITY: CREATING MEANINGFUL LEARNING EXPERIENCES (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract The objectives of this paper were to find out and analyze the concept of significant learning appropriately which could support higher education involvement to prepare students to adapt in educational community. Descriptive-qualitative approach was used in this paper. The result of the paper showed that firstly, there were six domains of meaningful learning at higher education which had relational connection and interactive activity, namely; foundation knowledge, application, integration, human dimension, caring, and learning how to learn. Secondly, to implement it, there were three steps for meaningful learning; they were (a) building significant main components; (b) arranging the components to a rational component holistically; and (c) finishing other important final tasks.Keywords: Higher Education Involvement, Educational Community, Meaningful Learning